Long-term Trends in the Population Ecology of Polar Bears in Western Hudson Bay in Relation to Climatic Change - Stirling, Ian; Lunn, Nicholas J.; Iacozza, John (ARCTIC, 1999)
From 1981 through 1998, the condition of adult male and female polar bears has declined significantly in western Hudson Bay, as have natality and the proportion of yearling cubs caught during the open water period that were independent at the time of capture. Over this same period, the breakup of the sea ice on western Hudson Bay has been occurring earlier. There was a significant positive relationship between the time of breakup and the condition of adult females (i.e., the earlier the breakup, the poorer the condition of the bears). The trend toward earlier breakup was also correlated with rising spring air temperatures over the study area from 1950 to 1990. We suggest that the proximate cause of the decline in physical and reproductive parameters of polar bears in western Hudson Bay over the last 19 years has been a trend toward earlier breakup, which has caused the bears to come ashore in progressively poorer condition. The ultimate factor responsible for the earlier breakup in western Hudson Bay appears to be a long-term warming trend in April-June atmospheric temperatures. De 1981 à la fin de 1998, la condition physique de l'ours polaire adulte, mâle et femelle, s'est détériorée de façon importante dans l'ouest de la baie d'Hudson, tout comme le nombre de naissances et la proportion d'oursons de l'année pris durant la période d'eau libre, et qui étaient indépendants au moment de leur capture. Au cours de la même période, la débâcle de la banquise sur l'ouest de la baie d'Hudson s'est produite plus tôt. Il existait un lien très marqué entre le moment de la débâcle et la condition physique des femelles adultes (c.-à-d. que plus la débâcle se produisait tôt, plus les ourses étaient en mauvaise condition physique). La tendance à une débâcle précoce était également corrélée à l'augmentation de la température ambiante printanière dans la zone d'étude de 1950 à 1990. On suggère que la cause immédiate du déclin des paramètres physiques et reproducteurs de l'ours polaire dans l'ouest de la baie d'Hudson au cours ...